Status of southern right whales (Eubalaena australis) off Australia - Bannister, John (J. Cetacean Res. Manage., 2020)
The history of Australian right whaling is briefly reviewed. Most catching took place in the first half of the 19th century, with a peak in the 1830s, involving bay whaling by locals and visiting whaleships in winter and whaling offshore in the summer. In the early 20th century, right whales were regarded as at least very rare, if not extinct. The first published scientific record for Australian waters in the 20th century was a sighting near Albany, Western Australia, in 1955. Increasing sightings close to the coast in winter and spring led to annual aerial surveys off southern Western Australia from 1976. To allow for possible effects of coastwise movements, coverage was extended into South Australian waters from 1993. Evidence from 19th century pelagic catch locations, recent sightings surveys, 1960s Soviet catch data and photographically-identified individuals is beginning to confirm earlier views about likely seasonal movements to and from warm water coastal breeding grounds and colder water feeding grounds. Increase rates of ca 7-13% have been observed since 1983. Some effects of different breeding female cohort strength are now beginning to appear. A minimum population size of ca 700 for the period 1995-97 is suggested for the bulk of the ‘Australian’ population, i.e. animals approaching the ca 2,000km of coast between Cape Leeuwin, Western Australia and Ceduna, South Australia.